Arts-Based Service Learning with Australian First Peoples: Concepts and considerations - Bennett, Dawn; Johnston, M.; Mason, B.; Thomson, C. (Springer, 2015)
In this introductory chapter we define some of the key concepts and considerations when engaging First Peoples in arts-based service learning. To do this we draw on a wide range of international literature. We then introduce the nation-wide Australian project that provided the groundwork, framework and inspiration for this edited volume. Lastly, we introduce the content and structure of the volume and outline each of the chapters’ key themes.